Disclosures in integrated reporting in Indonesia: Do corporate governance and ownership structures matter? - Yanto, Heri; Hajawiyah, Ain; Baroroh, Niswah; Arham, Ahmad Fadhly bin (International Journal of Management and Sustainability, 2024)
This study aims to analyze the impact of corporate governance and ownership structure on implementing elements of integrated reporting (IR) in the annual reports and sustainability reports of firms in Indonesia. This study includes corporate governance elements such as the size of the board of directors, the independence of the board of commissioners and the presence of audit and risk management committees. Meanwhile, the ownership structures examined in this study are institutional ownership and managerial ownership. The data were obtained through the content analysis of firms’ annual and sustainability reports. This research uses secondary data from the firms’ websites and the Indonesia Stock Exchange (IDX) website. The data were then analyzed further using multiple regression analysis. The results show that only the risk management committee positively affects IR disclosure. At the same time, other independent variables do not affect IR disclosure. All control variables positively affect IR disclosure. This study adds to the literature by demonstrating that the risk management committee, firm size, profitability and leverage influence the extent of integrated reporting disclosure. This research contributes to corporations by illustrating that a risk management committee can enhance the importance of IR disclosure in Indonesia.